Fabrication and Characterization of a Novel Composite Magnetic Photocatalyst β-Bi2O3/BiVO4/MnxZn1−xFe2O4 for Rhodamine B Degradation under Visible Light - Yong Cheng; Yahan Yang; Zao Jiang; Longjun Xu; Chenglun Liu (Nanomaterials, 2020)
β-Bi2O3/BiVO4/MnxZn1−xFe2O4 (BV/MZF) composite magnetic photocatalyst was first synthesized using the hydrothermal and calcination method. BV/MZF was a mesoporous material with most probable pore size and specific surface area of 18 nm and 17.84 m2/g, respectively. Due to its high saturation magnetization (2.67 emu/g), the BV/MZF composite can be easily separated and recovered from solution under an external magnetic field. The results of photo-decomposition experiments show that the decomposition rate of Rhodamine B (RhB) by BV/MZF can reach 92.6% in 3 h under visible light. After three cycles, BV/MZF can still maintain structural stability and excellent pollutant degradation effect. In addition, analysis of the photocatalytic mechanism of BV/MZF for RhB shows that the p-n heterojunction formed in BV/MZF plays a vital role in its photocatalytic performance. This work has potential application in the future for solving environmental pollution.